Experiences of adult stroke survivors and their parent carers: a qualitative study. (March 2013) - Jones, Lisa; Morris, Reg
Objective: To explore the experiences of adult stroke survivors and their parent carers. Design: Qualitative methodology: interpretative phenomenological analysis. Setting: Six residential areas across England and south Wales. Participants: Six adult stroke survivors (aged 27–46), six mothers (aged 59–76) and five fathers (aged 55–76). Method: Semi-structured interviews to explore the relationship and interactions between parent and survivor prior to and after a stroke, with opportunities to explore both positive and negative changes. All interviews were transcribed and analysed by a six step interpretative phenomenological analysis process. Survivors, mothers and fathers were analysed as three separate groups and the results were synthesised. Results: Identical and interconnected themes emerged from the three groups, permitting synthesis into a single organising framework with four superordinate themes capturing the key issues for all three groups. The four superordinate themes were: 'emotional turmoil'; 'significance of parents'; 'negotiating independence versus dependence' and 'changed relationships'. Conclusions: Parents reported adjusting to caring with relative ease. Survivors did not adjust to being cared for with such ease and felt positioned in a child role. Balancing independence and dependence was a challenge for survivors and parents and is considered within a systemic theory framework. Implications for service developments and guidelines are considered.